Body as psychoanalytic object : clinical applications from Winnicott to Bion and beyond - Harrang, Caron (New York, NY : Routledge, 2021)
"This book explores the role of bodily phenomena in mental life and in the psychoanalytic encounter, encouraging further dialogue within psychoanalysis, philosophy, and the humanities, and contributing new clinical and theoretical perspectives to the recent resurgence of psychoanalytic interest in the body. Presented in six sections in which diverse meanings are explored, Body as Psychoanalytic Object focuses on the clinical psychoanalytic encounter and the body as object of psychoanalytic inquiry, spanning from the prenatal experience to death. The contributors explore key themes including mind-body relations in Winnicott, Bion, and beyond; oneiric body; nascent body in early object relations; body and psychosensory experience; body in breakdown; and body in virtual space. With clinical vignettes throughout, each chapter provides unique insight into how different analysts work with bodily phenomena in the clinical situation and how it is conceived theoretically. Building on the thinking of Winnicott and Bion, as well as contributions from French psychoanalysis, Body as Psychoanalytic Object offers a way forward in a body-based understanding of object relations theory for psychoanalysts and psychotherapists"--
Keywords: Winnicott, D. W. -- 1896-1971.; Bion, Wilfred R. -- 1897-1979.; Psychoanalysis; Body image; Mind and body; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health